High Voltage Stable Polyoxalate Catholyte with Cathode Coating for All‐Solid‐State Li‐Metal/NMC622 Batteries. Issue 42 (27th September 2020) - Pan, Xiangyu; Sun, Han; Wang, Zhaoxu; Huang, Hao; Chang, Qian; Li, Junpeng; Gao, Jian; Wang, Shaofei; Xu, Henghui; Li, Yutao; Zhou, Weidong
Abstract: The solid polymer electrolyte (SPE) is one type of the most promising solid‐state electrolytes for next‐generation solid‐state batteries, due to its good compatibility with Li‐metal, high flexibility, and safety. To compete with currently used conventional Li‐ion batteries in energy density, SPEs must be integrated with high energy density cathode of LiNi x Mn y Coz O2 ( x  + y  + z  = 1, 0.5 < x  < 1) (NMC). However, the application of SPEs with NMC is limited by the narrow redox window of single SPEs and interfacial decomposition of SPEs by NMC. To overcome these challenges, a strategy is proposed utilizing a polymeric‐catholyte/‐anolyte‐composed dual‐polymer electrolyte and a cathode coating: a low voltage stable polyether works as a separator and stabilizes the interface with Li‐metal, while a high voltage stable polyoxalate functions as the catholyte and NMC particles are precoated by TiO2 . This cell model not only widens the voltage window of the electrolyte system, but also protects the polyoxalate in the cathode from interfacial decomposition. With this strategy, cycling stability of all‐solid‐state Li‐metal/LiNi0.6 Mn0.2 Co0.2 O2 (NMC622) cells is significantly improved. Meanwhile, large volume expansions of deposited lithium on both the Li‐metal anode and the copper collector are observed, which deserve more attention in the investigation of all‐solid‐state cells. Abstract : A polymeric‐catholyte/‐anolyte‐composed dual‐polymer‐electrolyte system combined with a cathode coating is developed to be compatible with both low potential anodes and high potential cathodes, and suppresses the interfacial oxidation of polymers by LiNi0.6 Mn0.2 Co0.2 O2 (NMC622), respectively. With the help of this strategy, the cycling performance of all‐solid‐state Li metal/NMC622 cells is significantly improved.